2011
DOI: 10.1212/wnl.0b013e31823e9f2a
|View full text |Cite
|
Sign up to set email alerts
|

Computerized visual field defects in posterior cortical atrophy

Abstract: CVF defects were characterized by homonymous visual field defects or bilateral constriction. Eight of 9 patients progressed to probable or definite AD, but the CVF defects were distinctly different from those in typical AD. This observation probably reflects a posterior shift of cortical pathology to the primary and early secondary visual cortices in PCA. CVF testing should be considered in older patients with unexplained visual complaints, particularly when associated with difficulty driving, which may indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
4
22
0
2
Order By: Relevance
“…VFD in PPCD are characterized by homonymous visual field defects or bilateral constriction. This observation probably reflects a posterior shift of cortical pathology to the primary and early secondary visual cortices in PPCD (10) . VFD testing should be considered in older patients with unexplained visual complaints, particularly when associated with diffi culty driving, which may indicate the possibility of PPCD and prompt early neurobehavioral evaluation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…VFD in PPCD are characterized by homonymous visual field defects or bilateral constriction. This observation probably reflects a posterior shift of cortical pathology to the primary and early secondary visual cortices in PPCD (10) . VFD testing should be considered in older patients with unexplained visual complaints, particularly when associated with diffi culty driving, which may indicate the possibility of PPCD and prompt early neurobehavioral evaluation.…”
Section: Discussionmentioning
confidence: 84%
“…PPCD patients had low performance when compared to controls in low level visual functions of visual acuity and line orientation, suggesting that early visual processing areas including V1 were impaired, as well as higher level visual functions of contour integration, mediated by extrastria tal areas, and the most complex task of object rotation, relying on processing within inferior temporal, parietal, and frontal cortices (9) . Visual field defects (VFD) may also be found in PPCD (10) . VFD in PPCD are characterized by homonymous visual field defects or bilateral constriction.…”
Section: Discussionmentioning
confidence: 99%
“…McMonagle et al reported visual field defects at presentation in only 1/19 patients (McMonagle et al 2006), while Tang-Wai and colleagues detected field deficits in 19/40 patients at first evaluation (Tang-Wai et al 2004). Pelak et al found abnormalities in all 9 PCA patients screened with threshold computerized visual field perimetry (Pelak et al 2011), suggesting that field defects may be highly prevalent when ascertained with sensitive tools. Visual field defects in PCA most often consist of homonymous hemianopia or quadrantanopia, a pattern that is clearly distinct from the bilateral inferior constriction pattern described in amnestic AD (Trick et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…I senere stadier av sykdommen kan man hos de fleste pasienter påvise homonym hemianopsi, kvadrantanopsi eller bilateral innskrenkning av synsfeltet ved hjelp av synsfelttesting (15,16). Venstresidige, homonyme hemifeltdefekter er vanligst.…”
Section: Senere Stadiumunclassified